2015
DOI: 10.3402/gha.v8.28615
|View full text |Cite
|
Sign up to set email alerts
|

Preschool overweight and obesity in urban and rural Vietnam: differences in prevalence and associated factors

Abstract: BackgroundChildhood obesity may soon be an equally important health threat as undernutrition and infectious diseases. Accurate information about prevalence and risk factors of obesity in children is important for the design of prevention.ObjectiveThe aim of this study was to estimate prevalence of overweight and obesity for preschool children in two Vietnamese areas, one urban and one rural, and to identify risk factors.DesignA cross-sectional study was conducted in urban Dong Da and rural Ba Vi districts, Han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
3
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 19 publications
2
52
3
8
Order By: Relevance
“…However, the current study was lower than study reports from different countries; 20.1% in Kenya [8], 23.6% in Nigeria [10] and 21.1% in urban Vietnam [9]. The observed discrepancy might be due to socio-cultural variations like high socio-economic status in the previous studies.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…However, the current study was lower than study reports from different countries; 20.1% in Kenya [8], 23.6% in Nigeria [10] and 21.1% in urban Vietnam [9]. The observed discrepancy might be due to socio-cultural variations like high socio-economic status in the previous studies.…”
Section: Discussioncontrasting
confidence: 87%
“…Studies in developing countries have shown that the prevalence of overweight and obesity among children are increasing overtime and it varies from country to country 20.1% in Kenya [8], 21.1% in urban Vietnam [9], 23.6% in Nigeria [10], 9% in the Recife Metropolitan Region [11] and 8.42% in Punjab India [12]. …”
Section: Introductionmentioning
confidence: 99%
“…Findings revealed that consuming large amounts of food and eating fast food were associated with increased risk of child overweight and obesity [29]. Similarly, a cross-sectional study conducted with four- to six-year-old children in Malaysia found that children’s body mass index had a positive relationship with fast food intake and eating out [30].…”
Section: Resultsmentioning
confidence: 99%
“…13 Physical activity and screen time were measured using a slightly modified questionnaire that had been used in previous studies. 5 Physical activity consisted of outdoor and indoor physical activities. Indoor activities included activities spent inside the house and in the classroom, such as playing with friends, going up and down stairs, or doing homework.…”
Section: Methodsmentioning
confidence: 99%
“…4 Several studies also indicated that rural children spend more time being active outdoors than children living in urban areas. 5 Low levels of physical activity may be due to increased screen time activity among children. At present, children spend more time watching television and playing computer games, which leads to increased snacking habits.…”
Section: Introductionmentioning
confidence: 99%